Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpls.2022.1014643
|View full text |Cite
|
Sign up to set email alerts
|

Predicting spatial variability of species diversity with the minimum data set of soil properties in an arid desert riparian forest

Abstract: Species diversity has spatial heterogeneity in ecological systems. Although a large number of studies have demonstrated the influence of soil properties on species diversity, most of them have not considered their spatial variabilities. To remedy the knowledge gap, a 1 ha (100 m × 100 m) plots of arid desert riparian forest was set up in the Ebinur Wetland Nature Reserve (ELWNR) in the NW China. Then, the minimum data set of soil properties (soil MDS) was established using the Principal Component Analysis (PCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
1
0
Order By: Relevance
“…The only soil variable that correlated with diversity matrix was soil pH. However, this nding is contrary to the report of some authors who noted that species diversity to being predictors against soil variables in a non-linear relationship to improving the riparian ecosystems functionality and productivity (Li et al 2022). In riparian forest sites with high diversity indices, high community pliability could be preserved by the several interactions between vegetation and soil properties (Ding et al 2017).…”
Section: ; Tengfei Et Al 2021 Antonini Et Al 2022mentioning
confidence: 61%
“…The only soil variable that correlated with diversity matrix was soil pH. However, this nding is contrary to the report of some authors who noted that species diversity to being predictors against soil variables in a non-linear relationship to improving the riparian ecosystems functionality and productivity (Li et al 2022). In riparian forest sites with high diversity indices, high community pliability could be preserved by the several interactions between vegetation and soil properties (Ding et al 2017).…”
Section: ; Tengfei Et Al 2021 Antonini Et Al 2022mentioning
confidence: 61%
“…The RF and MLR tools have been identified as valuable supplementary methods to conventional soil property monitoring [54]. Previous research has utilized MLR and RF models for assessing species diversity spatial variability, optimizing crop selection, and establishing relationships between environmental factors and soil properties [24,55,56]. The results of the study indicated that the RF model outperformed the MLR model in terms of accuracy when applied to both the training and validation datasets, consistent with Wang et al [57] This can be attributed to the effectiveness of soluble major ions complex as a predictor for soil salinity.…”
Section: Discussionmentioning
confidence: 99%
“…We then calculated the Simpson index, which was used to assess the alpha diversity of species and reflect species diversity within the habitat. 21 The Simpson index was higher in the OA group than in the control group (P < 0.05), suggesting that OA enriched the gut flora alpha diversity in mice (Fig. 4d).…”
Section: Enhancement Of the Chsp Reduction In The Content Of Secondar...mentioning
confidence: 92%